A titanium dioxide/nitrogen-doped graphene quantum dot nanocomposite to mitigate cytotoxicity: synthesis, characterisation, and cell viability evaluation. Issue 37 (10th June 2020) - Ramachandran, Pravena; Lee, Chong Yew; Doong, Ruey-An; Oon, Chern Ein; Kim Thanh, Nguyen Thi; Lee, Hooi Ling
Abstract : Cytotoxicity mitigation using titanium dioxide/nitrogen-doped graphene quantum dot nanocomposites. Abstract : Titanium dioxide nanoparticles (TiO2 NPs) have attracted tremendous interest owing to their unique physicochemical properties. However, the cytotoxic effect of TiO2 NPs remains an obstacle for their wide-scale applications, particularly in drug delivery systems and cancer therapies. In this study, the more biocompatible nitrogen-doped graphene quantum dots (N-GQDs) were successfully incorporated onto the surface of the TiO2 NPs resulting in a N-GQDs/TiO2 nanocomposites (NCs). The effects of the nanocomposite on the viability of the breast cancer cell line (MDA-MB-231) was evaluated. The N-GQDs and N-GQDs/TiO2 NCs were synthesised using a one- and two-pot hydrothermal method, respectively while the TiO2 NPs were fabricated using microwave-assisted synthesis in the aqueous phase. The synthesised compounds were characterised using Fourier transform infrared (FTIR) spectroscopy, high-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FESEM) and UV-visible spectrophotometry. The cell viability of the MDA-MB-231 cell line was determined using a CellTiter 96® AQueous One Solution Cell Proliferation (MTS) assay. The obtained results indicated that a monodispersed solution of N-GQDs with particle size 4.40 ± 1.5 nm emitted intense blue luminescence in aqueous media. The HRTEM images clearly showed that the TiO2 particles (11.46 ± 2.8 nm) are square shaped. Meanwhile, TiO2 particles were located on the 2D graphene nanosheet surface in N-GQDs/TiO2 NCs (9.16 ± 2.4 nm). N-GQDs and N-GQDs/TiO2 NCs were not toxic to the breast cancer cells at 0.1 mg mL −1 and below. At higher concentrations (0.5 and 1 mg mL −1 ), the nanocomposite was significantly less cytotoxic compared to the pristine TiO2 . In conclusion, this nanocomposite with reduced cytotoxicity warrants further exploration as a new TiO2 -based nanomaterial for biomedical applications, especially as an anti-cancer strategy.